Online peer-led intervention to improve adolescent wellbeing during the COVID-19 pandemic: a randomised controlled trial - Gabriela Pavarini; Tessa Reardon; Geoffrey Mawdsley; Ilina Singh (BMC, 2024)
Abstract Background The COVID-19 pandemic and associated lockdown measures have posed a major risk to young people's wellbeing, which might be ameliorated by peer-led programmes. Using a randomised controlled trial (ISRCTN registry, number ISRCTN77941736 https://doi.org/10.1186/ISRCTN77941736 ), we tested the short-term efficacy of an online peer-led intervention designed to equip young people with skills to support their mental health and wellbeing during the COVID-19 pandemic. Methods Through schools and social media ads, we recruited one hundred young people (aged 16-18) in the UK, focusing on areas with the highest incidence of COVID cases. In December 2020, participants were randomly allocated (1:1) to immediate 5 day Coping during COVID course (n = 49) or a wait-list (n = 51) through a survey software automated randomisation tool. Our primary outcome was self-reported mental wellbeing, and secondary outcomes included self-reported social connectedness, coping skills, sense of purpose, self-esteem, and self-compassion. We also collected qualitative reports of participants' perceived impact of the course and intentions to use what they have learnt from the course in their life moving forward. Assessments were completed at baseline, 1 week post randomisation (primary endpoint), and 2-weeks post-randomisation. Results Young people allocated to the peer-led intervention reported significantly greater wellbeing, social connectedness, coping skills, sense of purpose, self-esteem, and self-compassion 1 week and 2 weeks post-randomisation (medium-large effect sizes). Specific benefits to mental health, sense of purpose and connectedness were also emphasised in qualitative reports. Conclusions An online, peer-led intervention targeting youth wellbeing during the context of the COVID-19 pandemic brought benefits across a range of outcomes, suggesting that structured programmes that incorporate peer-to-peer support can be a valuable approach to promote young people's wellbeing and foster psychological resources during a health crisis.